Das noites clandestinas: poema sujo como vestígios informacionais e rastros testemunhais de um exilado da ditadura militar - Jonathan Kaefer Gomes da Costa (2022)
Starting from the premise that the literary text can be treated as a document, the present research sought to answer the following problem question: what elements allow us to perceive the Poema sujo (Dirty Poem), written by Ferreira Gullar during his exile, as a document that bears and mobilizes a set of informational resources and testimonial traces which reveal the implications of the military dictatorships – Brazilian and Southern Cone – on the poet's life and also on the country's history? In view of this, the following specific objectives were defined: a) to perform a bibliographic study, based on the concepts of traces and resources, focused on discussing in which conditions poetry can constitute an "archive" that organizes, preserves and perpetuates the historical memory of an era; b) to present and systematize the main themes mobilized by Ferreira Gullar in the conception of Poema sujo, thus seeking to highlight the informational resources and testimonial traces concerning his life experiences and the historical facts that occurred in the context of the Brazilian and Southern Cone military dictatorships; and c) to analyze to what extent the informational resources and testimonial traces present in Poema sujo can be perceived as references that document and mobilize the historical memory of the Brazilian military dictatorship. To this end, an exploratory study, of a bibliographic and documentary nature, was performed, supported by hermeneutic analysis in order to highlight 3 (three) categories of informational resources and testimonial traces triggered by Ferreira Gullar in order to produce wrinting about himself, namely: i) the beginning of the political journey of the man Gullar and his subsequent exiled status; ii) the poet's quest to identify himself as a body that occupies a place in the world and that seeks to resist his own disappearance; iii) the existing correlations between the mnemic gesture instituted by the poetic voice of Poema sujo and the territorialization of the author’s memories – from childhood to adulthood, from the city of São Luís and from Brazil – as a resource for avoiding the fragmentation of identity markers triggered by the poet in this once in a lifetime writing. As a result, it was demonstrated that Gullar's poetic account brings together many informational resources and testimonial traces capable of offering readers a better delineated image of the writer's life story, the reasons and inspirations that led to its creation, as well as the historical contingencies that guided individual actions and political events in Brazil and in other Southern Cone countries, in the context of the 1960s and 1970s.